جريمة تزوير المحررات في القانون 24-02 - بوبعاية سماح - بن اعمارة وداد (جامعة المسيلة, 2025)
Documents are one of the fundamental pillars of legal and administrative life. Their importance is closely linked to the skills of writing and reading, and they are included in various areas of human interaction, especially in the administrative field, where administrative documents constitute the cornerstone of all legal and official transactions and represent the primary key to proving actions and rights. Indeed, a person's life begins with one official document and ends with another. Given the widespread circulation of these documents, they may be subject to tampering or alteration, making them vulnerable to the crime of forgery, a serious crime that affects the public trust that must exist in official documents
Keywords: Editors; forgery; imitation.